The impact of social context on the perception of dental appearance in 8-9 years old children (Italian Journal of Public Health, 2009)
Background: Several studies have tried to clarify the role that malocclusion has on an individual’s selfconcept or on level of satisfaction with one’s dental or facial appearance, but little research on psycho-social attitudes towards malocclusion has been conducted on pre-adolescent children. The aim of our study was to investigate the impact of socio-economic status (SES) on the perception of dental appearance in third-grade school-children.Methods: A pilot survey was conducted in 2008 in order to collect data from a representative sample of 101 eight-nine years-old children (62 M - 39 F), examined by trained orthodontists. Each child filled in the Children’s Orthodontic Attitude Survey (COAS) questionnaire, and then they were examined by 3 residents. The clinical parameters were correlated with the questionnaire findings and with the SES. The latter was assessed using a previously validated scale, graded into classes from I to V reflecting the parents’ job activity. Statistical analysis: Statistical analysis was performed by using SPSS 12.0 for Windows, using Chi Square Test for nominal variables and Kruskal-Wallis test for ordinal scales. Statistical significance was set at p < 0.05.Results: A statistical association was found between clinical status and SES only for the Oral Hygiene level (p = 0.022). Chi-Square test also showed a statistically significant association between SES and R.O.M.A. Index (p = 0.009). The relation between questionnaire findings and SES was significantly observed only for the following question “Does the way your teeth look bother you” (p = 0.022).Conclusions: Familial SES is not a determinant in children’s satisfaction with dental appearance. Children with different SES demonstrate they have almost completely the same approach towards braces.
Keywords: Self-perception; malocclusion; aesthetics; behavioural; orthodontics